Primjena statistike u interdisciplinarnom kontekstu / Application of Statistics in a Multidisciplinary Context: Migriranje u SAD / Migrating to the USA - Repišti, Selman; Imamović, Ilda (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Migration is a topic that never loses its topicality. Most part of contemporary migration is driven by the possibility of commencing a new, safer life, that of a higher quality in another, more prosperous country than the home country. Hence, the main aim of this paper is to examine economic, geopolitical, sociological, and psychological determinants of migration into one of the most prosperous countries in the world (the USA). We examined the association between seven variables (education index, GDP, index of global peace, freedom of making life choices, corruption perception, positive affect, and the unemployment rate) and the ratio of the ''Green Card Lottery'' applicants to the population size of 41 European countries, for the year 2013. It turned out that the ratio of applicants for green card is higher if the education index, freedom of making decisions about their life, positive affect, and gross domestic product of European countries is low, whilst their instability and insecurity is high. All variables, taken together, are negatively associated with the desire and needs of the population of European countries to migrate to the United States. Additionally, the variables listed are, thus, a representative set of the prosperity indicators of each country.